Organizational citizenship behavior evaluation: Insights from Local Government Agency in Malaysia - Rashidah, Mohamad Ibrahim; Mazuri, Abd Ghani; Noorul Hafizah, Hashim (Medwell Journals, 2016)
The local government, the third-tier in Malaysian government structure, has been identified as one of the important government agencies mandated to drive the economic growth and development of a particular district and its residents. Since local governments, in general are faced with financial and administrative constraint that could jeopardize the operational efficiencies, Organizational Citizenship Behavior (OCB) is the identified vehicle to promote overall organizational effectiveness at a relatively low cost. A preliminary study on a local government agency was conducted using structural equations modeling Partial Least Squares (PLS) approach.Statistical analysis on measurement model in assessing reliability and validity and structural model in testing the hypothesized relationship provided indicative support of a good model in predicting Organizational Citizenship Behavior (OCB).